Effect of nano calcium carbonate from Anadara granosa shell induced odontoblast-like cells as a pulp capping material candidate - Saraswati, Widya; Ismiyatin, Kun; Goenharto, Setyabudi; Kunarti, Sri; Zubaidah, Nanik; Halima, Siti Noorraida; Daradjat, Kinanti Naianuha; Gusniarti, Haninda Dhipta (Conservative Dentistry Journal, 2025)
Background: Vital pulp therapy is a treatment to repair and maintain pulp vitality. Calcium hydroxide is the gold standard in pulp capping materials. Calcium hydroxide has advantage antibacterial. However, calcium hydroxide has some disadvantages such form a layer liquefaction necrosis. Blood clam shells contain 98.7% calcium carbonate. Calcium carbonate (CaCO3) content becomes a good source of calcium can be used as a bone repair material. Purpose: To review effect nano CaCO3 from Anadara granosa shell induced odontoblast-like cells as a pulp capping candidate. Nanoparticles CaCO3 has advantages such as high surface area, low toxicity, biocompatibility, biodegradability, pH-sensitivity, and osteoconductivity. Reviews: Nano CaCO3 from Anadara granosa are promising to promote odontoblast-like cells formation. Conclusion: Nano CaCO3 its potential to influence odontoblast-like cells, which play a crucial role in dentin regeneration and repair.